2014
DOI: 10.1002/eqe.2524
|View full text |Cite
|
Sign up to set email alerts
|

Characterizing friction in sliding isolation bearings

Abstract: The force-displacement behavior of the Friction Pendulum ™ (FP) bearing is a function of the coefficient of sliding friction, axial load on the bearing and effective radius of the sliding surface. The coefficient of friction varies during the course of an earthquake with sliding velocity, axial pressure and temperature at the sliding surface. The velocity and axial pressure on the bearing depend on the response of the superstructure to the earthquake shaking. The temperature at an instant in time during earthq… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
110
0

Year Published

2016
2016
2020
2020

Publication Types

Select...
5
3

Relationship

1
7

Authors

Journals

citations
Cited by 143 publications
(111 citation statements)
references
References 9 publications
1
110
0
Order By: Relevance
“…Regarding the friction which is the most important characteristic for the operation of the FP bearing, rigid contact is used to model the interfaces between the isolators' parts. In literature [17] it has been thoroughly investigated the influence of the friction models adopted for the analyses. Comparing Coulomb friction model with other more sophisticated which took into account the sliding velocity [6], the pressure or the temperature, have been concluded that the Coulomb friction is adequate to simulate the friction of the sliding surfaces of a FP bearing.…”
Section: Finite Element Modelingmentioning
confidence: 99%
“…Regarding the friction which is the most important characteristic for the operation of the FP bearing, rigid contact is used to model the interfaces between the isolators' parts. In literature [17] it has been thoroughly investigated the influence of the friction models adopted for the analyses. Comparing Coulomb friction model with other more sophisticated which took into account the sliding velocity [6], the pressure or the temperature, have been concluded that the Coulomb friction is adequate to simulate the friction of the sliding surfaces of a FP bearing.…”
Section: Finite Element Modelingmentioning
confidence: 99%
“…More specifically, a plethora of studies have been presented in the literature addressing the dependence of the friction coefficient upon contact pressure, sliding velocity and repetition of cycles that induces temperature rise at the sliding interfaces, see e.g. [3,5,9,10,11,13,14,17] just to quote a few. The common backbone of these studies is to alert the structural designer against oversimplification of the FPS behavior at the modeling stage.…”
Section: Critical Remarks On the Unidirectional Model With Coulomb Frmentioning
confidence: 99%
“…In particular, experimental results indicate that the dynamic-slow friction coefficient can be assumed 2.5 times lower than μfast [17], while parameter can be considered equal to approximately 0.1 s/mm [5].…”
Section: Calvfc1 Model: Constant Axial Load and Variable Friction Coementioning
confidence: 99%
“…BIA.MFT and BIB.MFT) friction properties by taking into account the dependence of the dynamic-fast friction coefficient on the heating at the sliding surface when the slider is in motion. To this end, a reduction factor kT of the friction coefficient [5] , 0.02…”
Section: Test Structures and Selected Earthquakesmentioning
confidence: 99%
See 1 more Smart Citation